2006
DOI: 10.1080/09537100500444063
|View full text |Cite
|
Sign up to set email alerts
|

The free-radical scavenger, edaravone, augments NO release from vascular cells and platelets after laser-induced, acute endothelial injuryin vivo

Abstract: In vitro and in vivo experimental models have demonstrated that vascular endothelial function is significantly impaired as a result of oxidative stress, mediated by the generation of oxygen-derived free radicals in response to chronic or acute inflammation. In particular, super-oxide () at specific concentrations leads to the impairment of nitric oxide (NO) bioactivity, and it is known that NO plays a fundamental role in the maintenance of vascular homeostasis. The relationship between reactive oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
(25 reference statements)
1
15
0
Order By: Relevance
“…Indeed, accumulating evidence suggests that edaravone modulates inflammatory processes, matrix metalloproteinase levels, and nitric oxide production in addition to its free radical-removing effect (34). In particular, a recent report provided direct evidence to confirm that edaravone promotes nitric oxide synthesis/ release following acute endothelial damage in peripheral microvessels, thus indicating it to have a beneficial effect on some neurodegenerative disorders (35). In addition, previous reports of ours indicated that endogenous or exogenous nitric oxide promotes the proliferation of NPCs derived from the embryonic mouse hippocampus (28,36) as well as from the dentate gyrus of the adult mouse (data not shown).…”
Section: DIVsupporting
confidence: 58%
“…Indeed, accumulating evidence suggests that edaravone modulates inflammatory processes, matrix metalloproteinase levels, and nitric oxide production in addition to its free radical-removing effect (34). In particular, a recent report provided direct evidence to confirm that edaravone promotes nitric oxide synthesis/ release following acute endothelial damage in peripheral microvessels, thus indicating it to have a beneficial effect on some neurodegenerative disorders (35). In addition, previous reports of ours indicated that endogenous or exogenous nitric oxide promotes the proliferation of NPCs derived from the embryonic mouse hippocampus (28,36) as well as from the dentate gyrus of the adult mouse (data not shown).…”
Section: DIVsupporting
confidence: 58%
“…In clinical els [13][14][15][16][17] . These stimulations are presumed to produce free radicals to injure endothelial cell function [18][19][20] ; however, the detailed physiological mechanism resulting in formation of arterial occlusive thrombi is yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…18 It is considered that edaravone prevents new thrombus formation by enhancing the expression of endothelial nitric oxide synthase, improving NO release, and inhibiting the expression of selection. 19 An increased NO level leads to vasorelaxation, and downregulation of the selection level suppresses platelet adhesion, platelet aggregation, and leukocyte adhesion. 20 Therefore, it was expected that edaravone would accelerate early recanalization.…”
Section: Discussionmentioning
confidence: 99%